Challenges and perspectives on sugar cane in Tamaulipas - Castro-Nava, Sergio (Universidad Autónoma de Tamaulipas, 2010)
The population growth and the constant demand for food and energy, climate change and issues for the use of fossil fuels, have raised the need to seek alternative sources of energy (ethanol) to cover those gaps. The most viable alternative is the sugar cane cultivation and now is one of the most important economic activities in Mexico, but it is necessary that the Mexican sugar industry resolves the current problems, for which we suggest the development of research areas, not enough to produce sugar cane, it is necessary to find and produce new products with cost-effective use of large volume. Sugar cane is also able to obtain sugar by-products of high economic value such as ethanol, xylitol, bagasse and filter cake, among many others. However, diversification should be through the interaction of multiple disciplines, not a single professional work, or a single institution. In other words, sugar cane provides a great opportunity in the near future, for the economic development of Tamaulipas to be a highly profitable crop and allows a wide range of production, but above all, an opportunity for development in various research areas interdisciplinary that contribute to technological development.